Personality Has Minor Effects on Panel Attrition - David Richter; John L. Körtner; Denise Saßenroth (Journal of Research in Personality, 2014)
Abstract In light of the recent interest in using longitudinal panel data to study personality development, it is important to know if personality traits are related to panel attrition. We analyse the effects of personality on panel drop-out separately for an `older' subsample (started in 1984), a relatively `young' subsample (started in 2000), and a `new' subsample (started in 2009) of the German Socio-Economic Panel (SOEP) study. We found that openness slightly decreases the probability of panel drop-out in all three samples. For the `older' subsample only, we found a small negative effect of agreeableness on panel drop-out. We control for age, sex, education, migration background, and the number of inhabitants in the region of the respondents.
Additional information: NOTICE: This is the author's version of a work that was accepted for publication in the Journal of Research in Personality. Changes resulting from the publishing process, such as peer review, editing, corrections, structural formatting, and other quality control mechanisms may not be reflected in this document. Changes may have been made to this work since it was submitted for publication. A definitive version was subsequently published in the Journal of Research in Personality, 53 (2014), pp. 31-35 and is online available at http://dx.doi.org/10.1016/j.jrp.2014.08.001.
Keywords: 330; Personality; Panel attrition; German Socio-Economic Panel Study